2004
DOI: 10.1255/ejms.628
|View full text |Cite
|
Sign up to set email alerts
|

Gas-Phase Ion–Molecule Reactions of Small Nitroalkanes and Their Deprotonated Anions

Abstract: Gas-phase reactions of nitromethane (1), nitroethane (2), 2-nitropropane (3), 2-methyl-2-nitropropane (4) and nitrocyclopropane (5) were studied at 300 K using the flowing afterglow technique. These nitroalkanes react with gas-phase bases HO(-), CH(3)O(-) and HOO(-) very rapidly with rate coefficients of (2.5-4.3) x 10(-9) cm(3) s(-1) and reaction efficiencies of 60-100%, for example, k = 3.2 x 10(-9) cm(3) s(-1) (86%) for 5 reacting with hydroperoxide anion. Proton transfer (PT) is the only reaction observed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
31
0

Year Published

2004
2004
2015
2015

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(31 citation statements)
references
References 38 publications
0
31
0
Order By: Relevance
“…Anions and radicals of those species are also considered important intermediates in combustion. The SIFT technique has been employed to study, through an anionic approach, the structure and thermochemistry of diazocarbene (CNN) and the diazomethyl radical (HCNN), 106) small nitroalkanes, 107) and a series of five-membered azole compounds. [CNN], which are conjectured to be combustion intermediates that provide low energy paths to cleave N 2 to produce N atoms (Scheme 7).…”
Section: We Also Studied Collision-induced Dissociation Of the [M῎h]mentioning
confidence: 99%
See 4 more Smart Citations
“…Anions and radicals of those species are also considered important intermediates in combustion. The SIFT technique has been employed to study, through an anionic approach, the structure and thermochemistry of diazocarbene (CNN) and the diazomethyl radical (HCNN), 106) small nitroalkanes, 107) and a series of five-membered azole compounds. [CNN], which are conjectured to be combustion intermediates that provide low energy paths to cleave N 2 to produce N atoms (Scheme 7).…”
Section: We Also Studied Collision-induced Dissociation Of the [M῎h]mentioning
confidence: 99%
“…157) We also demonstrated that negative ion chemistry with HO ῍ is an alternative tool to monitor plant emission of VOCs 158)ῐ160) and to detect small, volatile nitroalkane explosives. 107) These analytical applications and bio/ medico-chemical implications, as well as ionῐmolecule chemistry of interstellar relevance, will be discussed elsewhere. 161) A new reaction scheme of CIMS interest is given here.…”
Section: Chemical Ionization Mass Spectrometrymentioning
confidence: 99%
See 3 more Smart Citations